Association of cheese and yogurt intake with sleep duration in preschool-aged children: a 6-month prospective cohort study - Lin, Cuilan; Yang, Zhuling; Yuan, Yawen; Lai, Xin; Fu, Simao; Pan, Dongxue (Frontiers in Nutrition, 2026)
ObjectiveTo evaluate whether baseline cheese and yogurt intake is associated with sleep duration at baseline, 3- and 6-month follow-ups among preschool-aged children.MethodsWe conducted a prospective cohort study in Zhongshan City, Guangdong Province, China. Parents completed baseline questionnaires on cheese and yogurt intake frequency, sleep duration and potential confounders, with sleep time followed up at 3 and 6 months. Sleep duration of < 10 h per day was defined as insufficient. Multivariable logistic regression and mixed-effects models were used to evaluate the association between the baseline cheese and yogurt intake and sleep duration at baseline, 3- and 6-month follow-ups.ResultsA total of 221 preschool-aged children were included in the analysis. No significant association was found between yogurt consumption and sleep duration at any time point. For cheese intake, a significant trend was identified at 6 months (p = 0.007), and cheese intake ≥ 7 servings/week showed a reduced prevalence of insufficient sleep (adjusted OR = 0.001, 99.2% CI: 0.000–0.168). Mixed-effects models confirmed a significant interaction between high cheese intake and 6-month follow-up (OR = 0.217, 95% CI: 0.052–0.917).ConclusionOur findings suggest that frequent cheese intake may reduce the risk of insufficient sleep in preschool-aged children, whereas yogurt shows no comparable association. These differential results underscore the need for product-specific analyses. Despite limitations in sample size and measurement, the study adds to evidence linking diet, microbiota, and sleep. Further research should clarify underlying mechanisms and guide actionable, child-appropriate dietary recommendations.